1998
DOI: 10.1021/bi9802465
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes in the Core Structure of Bacteriorhodopsin

Abstract: Bacteriorhodopsin (bR) is the light-driven proton pump found in the purple membrane of Halobacterium salinarium. In this work, structural changes occurring during the bR photocycle in the core structure of bR, which is normally inaccessible to hydrogen/deuterium (H/D) exchange, have been probed. FTIR difference bands due to vibrations of peptide groups in the core region of bR have been assigned by reconstituting and regenerating delipidated bR in the presence of D2O. Exposure of bR to D2O even after long peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 58 publications
5
26
0
Order By: Relevance
“…This band is missing in the resonance Raman spectra of pR (40). In bacteriorhodopsin a similar band was attributed to an amide II response to isomerization (41). The appearance of a 1550 cm À1 band on a timescale on the order of tens of picoseconds was also observed for SRII (42) and halorhodopsin (43) and was interpreted as a relax- ation of protein vibrational bands, possibly amide II bands of the protein backbone, perturbed by the ultrafast retinal photoisomerization.…”
Section: Discussionmentioning
confidence: 82%
“…This band is missing in the resonance Raman spectra of pR (40). In bacteriorhodopsin a similar band was attributed to an amide II response to isomerization (41). The appearance of a 1550 cm À1 band on a timescale on the order of tens of picoseconds was also observed for SRII (42) and halorhodopsin (43) and was interpreted as a relax- ation of protein vibrational bands, possibly amide II bands of the protein backbone, perturbed by the ultrafast retinal photoisomerization.…”
Section: Discussionmentioning
confidence: 82%
“…A similar amide II downshift was observed in GPR (32) but only at room temperature on an ultrafast time scale. In contrast, in the low-temperature FTIR difference spectrum of BR, a pair of bands is assigned to the upshift of an amide II mode (41). …”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies on bacteriorhodopsin indicated that internal, core domains of bacterio‐opsin are much more accessible for H 2 O/D 2 O exchange after bleaching than in the native pigment with the chromophore in place, indicating a more open and hydrophilic structure (24). However, no changes in the protonation states of buried aspartates Asp96 and Asp115 were detected upon reconstitution, just an IR frequency shift indicating a more hydrophobic environment in the reconstituted state (25).…”
Section: Discussionmentioning
confidence: 99%